Analisis Kemampuan Membaca Kitab Kuning di PP. At-Taufiq Jombang - Siti Naimah; Nurul Hidayah; Lailatul Mathoriyah (Al-Lahjah, 2022)
This paper discusses the ability of students of PP. At-Taufiq Jombang in reading bald books. This paperis motivated by the method used in Boarding Schools to overcome the difficulty of students in readingbald books. Bald book is a tradition learned in Pondok Pesantren and has become a label in education inPondok Pesantren. Sorogan method is one of the methods in learning to read bald books. In this case theauthor aims to conduct research on the ability of students in PP. At-Taufiq Jombang in reading the baldbook which in his learning using the sorogan method. The method used in this study is descriptivequalitative research using (Field Research). The types of data used in this study are primary andsecondary data taken from related sources. The discussion showed the analysis in PP. At-TaufiqJombang in reading the bald book using sorogan method has reached a satisfactory value. This can beseen from the value of the research results to some students in PP. At-Taufiq Jombang.